2022
DOI: 10.1093/neuonc/noac278
|View full text |Cite
|
Sign up to set email alerts
|

Alternative lengthening of telomeres (ALT) in pediatric high-grade gliomas can occur without ATRX mutation and is enriched in patients with pathogenic germline mismatch repair (MMR) variants

Abstract: Background To achieve replicative immortality, most cancers develop a telomere maintenance mechanism, such as reactivation of telomerase or alternative lengthening of telomeres (ALT). There are limited data on the prevalence and clinical significance of ALT in pediatric brain tumors, and ALT-directed therapy is not available. Methods We performed C-circle analysis (CCA) on 579 pediatric brain tumors that had corresponding tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 46 publications
3
8
0
Order By: Relevance
“…Although previous studies have demonstrated potential connections between ATRX / DAXX mutations, H3-3A G34R/G34V mutations and ALT use, 6 patients with HGG in our cohort with ALT phenotype did not harbor H3.3K27M or G34R/V and/or ATRX mutations, suggesting acquisition of these alterations are not necessary or sufficient for the induction of ALT in HGG. Similar presence of ALT in pediatric HGG in the absence of ATRX mutations has recently been reported, 42 though continued investigation in a larger cohort is needed to further elucidate the mechanistic biology.…”
Section: Discussionsupporting
confidence: 54%
“…Although previous studies have demonstrated potential connections between ATRX / DAXX mutations, H3-3A G34R/G34V mutations and ALT use, 6 patients with HGG in our cohort with ALT phenotype did not harbor H3.3K27M or G34R/V and/or ATRX mutations, suggesting acquisition of these alterations are not necessary or sufficient for the induction of ALT in HGG. Similar presence of ALT in pediatric HGG in the absence of ATRX mutations has recently been reported, 42 though continued investigation in a larger cohort is needed to further elucidate the mechanistic biology.…”
Section: Discussionsupporting
confidence: 54%
“… 11 Another study harnessed the OpenPBTA to integrate germline variants, discovering that pediatric patients with HGG with alternative telomere lengthening are enriched for pathogenic or likely pathogenic germline variants in the MMR pathway, possess oncogenic ATRX mutations, and have increased TMB. 12 Moreover, the OpenPBTA has enabled a framework to support real-time integration of clinical trial subjects as they enrolled in the PNOC008 HGG clinical trial 75 or the PNOC027 MB clinical trial, 76 allowing researchers and clinicians to link tumor biology to translational impact through clinical decision support during tumor board discussions. Finally, as part of the NCI’s CCDI, the OpenPBTA was recently expanded into OpenPedCan, a pan-pediatric cancer effort ( https://github.com/PediatricOpenTargets/OpenPedCan-analysis ) that enabled the creation of the pediatric Molecular Targets Platform ( https://moleculartargets.ccdi.cancer.gov/ ) in support of the RACE Act.…”
Section: Discussionmentioning
confidence: 99%
“…Through the OpenPBTA, we present a comprehensive, collaborative, open genomic analysis of 1,074 tumors and 22 cell lines, comprised of 58 distinct brain tumor histologies from 943 patients. The data and containerized infrastructure of the OpenPBTA have already supported discovery and translational research studies, 9 , 10 , 11 , 12 are actively integrated into PNOC molecular tumor board decision-making, and have provided a foundational layer for the Childhood Cancer Data Initiative’s (CCDI) recently established pediatric Molecular Targets Platform ( https://moleculartargets.ccdi.cancer.gov/ ). We anticipate that the OpenPBTA will continue to be invaluable to the pediatric oncology community.…”
Section: Introductionmentioning
confidence: 99%
“…In GBM, ALT is more prevalent in pHGG (44–53%) compared to adult HGG (11%) [ 15 , 21 , 22 , 23 , 24 , 25 ]. ALT-positive adult GBM were reported to have longer survival times [ 23 , 25 ], however, no significant association between ALT status and OS has been observed in pHGG, probably due to small sample sizes and typical short survival times of pHGG patients, especially in H3.3K27M mutant pHGGs [ 21 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated potential connections between ATRX / DAXX, H3-3A (encoding for H3.3 histone variant) mutations and ALT use, especially in oligodendrogliomas, medulloblastomas, neuroblastomas and GBM [ 27 , 28 , 29 ]. However, the presence of ALT phenotypes in pHGG, adult pancreatic neuroendocrine tumors and melanoma in the absence of ATRX mutations has recently been reported [ 26 , 30 ], suggesting the acquisition of these alterations is not necessary for the induction of ALT. Further investigations are needed to elucidate the mechanistic biology of ALT in these tumors.…”
Section: Introductionmentioning
confidence: 99%